2022
DOI: 10.1088/1755-1315/972/1/012072
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short-circuit current in AC and DC shipboard electrical power distribution systems: A case study of 17,500 DWT tanker vessel

Abstract: The current ability of power electronic devices increases the possibility to change the shipboard electrical power distribution system from widely-used alternating current (AC) to direct current (DC) systems. DC distribution systems has been known to offer higher power efficiency compared with AC distribution systems. However, the decision to move the shipboard electrical power distribution systems to DC systems requires more information in technical aspects aside of power efficiency. In this study, the invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Nevertheless, the possibility to apply DC shipboard distribution system is still being studied continuously as the advantages are very tempting. Ongoing research involves feasibility studies with current technologies and also development of the technologies to allow the implementation [16]- [18].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the possibility to apply DC shipboard distribution system is still being studied continuously as the advantages are very tempting. Ongoing research involves feasibility studies with current technologies and also development of the technologies to allow the implementation [16]- [18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the addition of photovoltaic as a power source will increase the value of the short circuit current in the existing system [6].…”
Section: Introductionmentioning
confidence: 99%
“…According to the Classification Code for Steel Sea-going Vessels (2022) and Closed-loop Power Positioning System Inspection Guidelines (2020) issued by the China Classification Society (CCS), all newly built ships must undergo a short-circuit testing within the ship's electrical power system. Gumilang et al [3] simulated a certain 17, 500 DWT tanker power distribution system by using software and indicated that, for the same ship, the short-circuit current of the DC power distribution system is lower than that of the AC power distribution system. In this paper, using Simulink simulation software and a 300, 000 DWT oil tanker as an example, we simulate the short-circuit faults during the ship's electrical power system operations and analyze how the faults affect the stability in the marine…”
Section: Introductionmentioning
confidence: 99%